Coming to Common Ground: The Challenges of Applying Ecological Theory Developed Aboveground to Rhizosphere Interactions - Shelef, Oren; Hahn, Philip G.; Getman-Pickering, Zoe; Martinez Medina, Ainhoa (Frontiers in Ecology and Evolution, 2019)
Accumulating evidence supports the importance of belowground interactions for plant performance, ecosystem functioning, and conservation biology. However, studying species interactions belowground has unique challenges relative to the aboveground realm. The structure of the media and spatial scale are among the key aspects that seem to strongly influence belowground interactions. As a consequence, our understanding of species interactions belowground is limited, at least compared to what is known about interactions aboveground. Here we address the general question: Do the ecological concepts that have been developed largely in aboveground systems apply to understanding species interactions in the rhizosphere? We first explore to what extent ecological concepts related to species interactions are considered in rhizosphere studies across various subdisciplines. Next, we explore differences and similarities above- and belowground for fundamental concepts in ecology, choosing topics that are underrepresented in rhizosphere studies but represent a swath of concepts: species diversity, island biogeography, self-organization and ecosystem engineering, trophic cascades, and chemical communication. Finally, we highlight to overcome major challenges of current methodologies to study rhizosphere interactions in order to advance the understanding of belowground interactions in an ecological context. By synthesizing literature related to rhizosphere interactions, we reveal similarities, as well as key differences, in how fundamental ecological concepts are used and tested in above- and belowground studies. Closing the knowledge gaps identified in our synthesis will promote a deeper understanding of the differences above- and belowground and ultimately lead to integration of these concepts.